2001
DOI: 10.1095/biolreprod64.3.904
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Distribution and Adenosine Triphosphate Content of Bovine Oocytes Before and After In Vitro Maturation: Correlation with Morphological Criteria and Developmental Capacity After In Vitro Fertilization and Culture1

Abstract: In this study, we evaluated mitochondrial distribution and ATP content of individual bovine oocytes before and after in vitro maturation (IVM). Cumulus-oocyte complexes were classified according to morphological criteria: category 1, homogeneous oocyte cytoplasm, compact multilayered cumulus oophorus; category 2, cytoplasm with small inhomogeneous areas, more than five layers of compact cumulus; category 3, heterogeneous/vacuolated cytoplasm, three to five layers of cumulus including small areas of denuded zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

39
348
12
23

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 442 publications
(422 citation statements)
references
References 27 publications
39
348
12
23
Order By: Relevance
“…In our study, we did not find differences in mitochondrial distribution between BCB oocyte groups, while Egerszegi et al (2010) concluded that, in pigs, BCBK oocytes showed more heterogeneous and non-aggregated mitochondrial distribution than BCBC oocytes. Different authors have reported differences in mitochondrial distribution patterns among species, during IVM and in vivo maturation (Stojkovic et al 2001, Sun et al 2001, Torner et al 2004, Velilla et al 2006, Dell'Aquila et al 2009, Egerszegi et al 2010. Previous studies showed that GV-oocytes do not present MPF activity (Dedieu et al 1996) but, in our study, we detected MPF activity before IVM; this may be due to the BCB staining time.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…In our study, we did not find differences in mitochondrial distribution between BCB oocyte groups, while Egerszegi et al (2010) concluded that, in pigs, BCBK oocytes showed more heterogeneous and non-aggregated mitochondrial distribution than BCBC oocytes. Different authors have reported differences in mitochondrial distribution patterns among species, during IVM and in vivo maturation (Stojkovic et al 2001, Sun et al 2001, Torner et al 2004, Velilla et al 2006, Dell'Aquila et al 2009, Egerszegi et al 2010. Previous studies showed that GV-oocytes do not present MPF activity (Dedieu et al 1996) but, in our study, we detected MPF activity before IVM; this may be due to the BCB staining time.…”
Section: Discussioncontrasting
confidence: 62%
“…This would indicate a positive relationship between mitochondrial activity at MII stage and embryo development. Stojkovic et al (2001) showed that mitochondrial reorganisation was different between morphologically good and poor quality oocytes. In our study, mitochondria migrated throughout the IVM process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could easily be explained by the fact that an embryo fully depends on maternal cytoplasm until the maternal embryonic genome transition takes place from the 8-to 16-cell stage, since no (or very few) mRNAs are formed until then (Rodriguez & Farin 2004). Fully mature cytoplasm of the oocyte provides the embryo with a battery of maternal mRNAs, proteins, and mitochondria, which are related to oocyte development competence and which may contribute to apoptotic pathways but also to defense mechanisms against apoptosis (Fair et al 1995, Otoi et al 1997, Stojkovic et al 2001. Microinjection of healthy cytoplasm protected oxidative-stressed zygotes from apoptotic death in mice (Liu & Keefe 2000) and improved fertility in older patients with compromised embryos in humans (Cohen et al 1998, Barritt et al 2001.…”
Section: Discussionmentioning
confidence: 99%